Technology for nanocomplexes of curcuminoids with cyclodextrins production, investigation of their properties and biological activity - Kapustin, Maxim A.; Chubarova, Hanna S.; Lodygin, Aleksei D.; Rzhepakovsky, Igor V.; Dudchik, Natalia V.; Tsygankow, Vasili G.; Kurchenko, Vladimir P. (Experimental Biology and Biotechnology, 2025)
Curcuminoids have a wide range of biological activity and pronounced therapeutic potential, but low bioavailability, which limits the possibility of their use. In order to increase the solubility and bioavailability of curcuminoids, an original technology for obtaining their nanocomplexes with cyclodextrins has been developed. In this regard, the method of extraction, purification and separation of curcuminoids by flash chromatography was optimised, and the isolated compounds were identified. The optimal values of temperature and concentration of cyclodextrins for the formation of nanocomplexes of curcuminoids with β-cyclodextrin (Cur : β-CD) and 2-hydroxypropyl-β-cyclodextrin (Cur : HP-β-CD) were established. Using the methods of IR spectroscopy and thermal analysis, changes in spectral properties and an increase in thermal stability of curcuminoids in nanocomplexes are shown: the activation energy of thermal destruction of curcuminoids in the composition of the Cur : β-CD and Cur : HP-β-CD nanocomplexes increased from (57.7 ± 2.9) to (217.4 ± 4.1) and (268.6 ± 9.4) kJ/mol, respectively. It was found that the antioxidant activity of curcuminoids in the series curcumin, bisdemethoxycurcumin, demethoxycurcumin is reduced compared to the antioxidant activity of trolox by 2.5, 3.2, 4.9 times, respectively. Using the Ames test, the antimutagenic activity of preparations of curcuminoids, Cur : β-CD and Cur : HP-β-CD nanocomplexes, was determined. It was noted that the application of the Cur : β-CD nanocomplexes as a wound healing agent in a rat skin flap wound model stimulated the reparative process along the path of organotypic regeneration. Composite nanofibrils based on pullulan and preparations of curcuminoids, Cur : β-CD and Cur : HP-β-CD nanocomplexes were obtained by electrospinning. The resulting original cover material can be used as wound healing agent.
Keywords: curcuminoids; nanocomplexes; nanostructures; cyclodextrins; thermal stability; antioxidant activity; antimutagenic activity; wound healing